Equivocal and Deceitful Didactic Poetry. What Style Matters Can Say About Empedocles’ Audience(s) - Andolfi, Ilaria (Revista Archai, 2024)
Since antiquity, Empedocles has been considered as an example of both successful and unsuccessful communication. Aristotle credits him with vividness of images, but blames him for failure of clarity, and eventually compares his obscureness to that of oracles. Therefore, scholars in the past came to the conclusion that Empedocles deliberately employs an opaque style, like Heraclitus and his “studied ambiguity”, as means for initiation. This paper challenges this assumption and asks whether and how ambiguity can work within a didactic poem. By showing how Empedocles’ and Heraclitus’ communicative strategies differ from one another, I shall point to the poet’s role as a charismatic and spiritual guide, displaying at times a Sibyl-like attitude. Being a mediator between two separate dimensions puts Empedocles in an ambiguous position, because he delivers what the Muse and the gods made available for him to share, and so his opaqueness does not come directly from him. Ultimately, this style analysis also says something about who the ideal audience must have been.